Navigating Environmental Stewardship: A Review of Construction Industry Practices in Developed Countries - Liong, Rachel; Binhudayb, Faisal Saud; Elshikh, Mohammed; Hesham, Salem (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2024)
Due to rapid urbanization, the construction industry has expanded significantly to meet human needs. Controlling environmental impacts in the construction sector has become a major global issue. The implementation of environmental management practices in the construction sector has contributed to protecting the environment through various management methods. This review aims to provide an overview of environmental management practices in the construction industry in developed countries, including a review of the types of environmental management practices and government policies for adopting these practices. The current status of these practices in developed countries is discussed, as well as the barriers and prospects for environmental management practices. Challenges include behavior adoption, lack of material standardization, monitoring difficulties, and inefficient formation of temporary organizations. Cooperation among construction parties presents coordination issues, exacerbating uneven cost distribution and neglect of environmental impacts. Adoption of ISO 14001 Environmental Management Systems faces hurdles such as lack of management involvement, third-party interference, and lack of guidelines. Initiatives like Green Star struggle due to poor enforcement and organizational issues, hindering sustainable development. To accomplish the goal of sustainable development, additional environmental factors have been taken into account and discussed.